2015
DOI: 10.1021/acs.jmedchem.5b00651
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Activity of Mononuclear Copper(II) Polypyridyl Complexes for the Treatment of Cancers

Abstract: A series of four new mononuclear copper(II) polypyridyl complexes (1-4) have been designed, developed, and thoroughly characterized by several physicochemical techniques. The CT-DNA binding properties of 1-4 have been investigated by absorption, emission spectroscopy, and viscosity measurements. All the complexes especially 1 and 4 exhibit cytotoxicity toward several cancer cell lines, suggesting their anticancer properties as observed by several in vitro assays. Additionally, the complexes show inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…Experiments were repeated >3 times. To detect ROS production, H 2 O 2 -treated HUVECs (1×10 5 cells) were incubated with the fluorescent probe 2′,7′-dichlorodihydrofluorescein diacetate (chloromethyl derivative) at 37°C for 30 min, as previously described ( 23 25 ). Subsequently, samples were digested by trypsin-EDTA solution (Beyotime Institute of Biotechnology), centrifuged (1,000 × g for 5 min at room temperature) and transferred to black 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments were repeated >3 times. To detect ROS production, H 2 O 2 -treated HUVECs (1×10 5 cells) were incubated with the fluorescent probe 2′,7′-dichlorodihydrofluorescein diacetate (chloromethyl derivative) at 37°C for 30 min, as previously described ( 23 25 ). Subsequently, samples were digested by trypsin-EDTA solution (Beyotime Institute of Biotechnology), centrifuged (1,000 × g for 5 min at room temperature) and transferred to black 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the development of metal complexes with nonplatinum central atoms including ruthenium [11], gold [12], silver [13], copper [14], zinc [15], Manganese [16], nickel [17], iridium [18] and cobalt [19] has been one of the hottest emerging areas of anticancer drug research. Among these, carbonyl cobalt complex has strong properties of cancer prevention including tumour growth/metastasis suppression [20], antiproliferative [21], DNA cleavage [22], apoptotic induction [23] and autophagy [8], which was more active than cisplatin on the human breast tumour cell lines (MCF-7 and MDA-MB-231) [24,25] and ovarian cancer cells (SKOV3/ DDP) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies by Sigman in the 1990s [9][10][11][12][13], and by Pitié and Meunier [14][15][16] and several others in recent years [17][18][19][20][21][22][23] indicate efficient DNA cleavage and cytostatic properties. Such compounds are also reported to display antiangiogenic activity [24]. Also, studies by some of us with Cu(II) compounds and tridentate pyridine-based ligands have shown very promising results for both DNA cleavage and anticancer activities [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%